The travel industry : image gap analysis - Goh, Hui Li (2014)
This report was motivated by the team's interest in the effectiveness of the marketing strategies of travel companies in promoting their companies' images and products. The perception congruence of travel companies and their consumers is used as a yardstick in this study. Six travel companies were chosen to be the research subjects. These companies advertise frequently in the local newspapers. They are Chan Brothers Travel Pte. Ltd (Chan Brothers), Commonwealth Travel Service Corporation Pte. Ltd. (CTC), Dynasty Travel International Pte. Ltd (Dynasty), Ken-Air Tours Pte. Ltd (Ken-Air), Oxley Travel Service Pte Ltd (Oxley) and Sino-America (UIC) Tours Corporation Pte. Ltd (SA(UIC)).